Music Therapy And Effective Communication Reduces Anxiety Levels In Welcoming Childbirth - Imelda Damanik; Feva Tridiyawati (International Journal of Health and Pharmaceutical (IJHP), 2023)
Labor pain is a physiological condition that can hinder the delivery process. Excessive pain can disturb the body's homeostasis which can result in excessive and useless energy. Reducing the pain scale can be done by fermacological and non-fermacological measures. It's normal for pregnant women and mothers to experience pain. Measuring the pain scale using the Numerical Rating Scale (NRS) and quasi-experiments. Music therapy is a form of implementation that uses music and songs in an integrated and directed manner to guide mothers in pregnancy with the aim that pregnant women feel relaxed, early stimulation of the fetus. Effective intrapersonal communication between a midwife can help a mother overcome depression during pregnancy and childbirth. It can also help patients stay positive throughout the pregnancy and delivery process, making it fun and easy to deal with issues that arise while raising a child. The anxiety level score in the pre-test measurement is higher than the post-test measurement, indicated by the mean value in the pre-test (22.67) higher than the post-test (16.77) which means that there is a decrease in the anxiety level score in the respondents before and after intervention. The results of this study were that there was a significant effect of classical music therapy on reducing the anxiety level of third-trimester pregnant women. This was evident from the statistical test used, the Wilcoxon Match Pairs Test, with a result (p=0.000) less than (<0.05). The researcher's assumption is that music therapy can distract pregnant women so as to reduce maternal anxiety in welcoming labor and effective communication between midwives and pregnant women can motivate pregnant women to be brave in facing labor and reduce anxiety in welcoming labor.